Phytochemical screening, antimicrobial and antidiabetic activity of n-hexane extract of Macaranga depressa leaves - KHOLIFATU ROSYIDAH; RAHMAT EKO SANJAYA; UTAMI IRAWATI; NAWWAL HIKMAH; RIZKY AULIA FITRIANI; JANNESA TRI ROSADI; IRAWAN WIJAYA KUSUMA; YADI YADI; AGNES V. SIMAMORA; ANTONIUS R. B. OLA; I GUSTI MADE NGURAH BUDIANA (Society for Indonesian Biodiversity, 2025)
Abstract. Rosyidah K, Sanjaya RE, Irawati U, Hikmah N, Fitriani RA, Rosadi JT, Kusuma IW, Yadi, Simamora AV, Ola ARB, Budiana IGMN. 2025. Phytochemical screening, antimicrobial and antidiabetic activity of n-hexane extract of Macaranga depressa leaves. Biodiversitas 26: 5156-5168. The Macaranga genus has been used in folk medicine to treat pathological disorders like diabetes. However, the chemical constituents and bioactivity of Macaranga depressa have never been studied. Thus, this study combined phytochemical profiling, antimicrobial evaluation, and in silico molecular docking of M. depressa. It aims to determine the phytochemical profile, antimicrobial, and antidiabetic activities of n-hexane extract of M. depressa leaves. Sample extraction was carried out by maceration method. The phytochemical profile of the plant was determined by phytochemical screening method and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) method. Antimicrobial activity was tested in vitro using disc diffusion method. Antidiabetic activity was tested in vitro and in silico including drug similarity analysis, ADME (Absorption, Distribution, Metabolism, and Excretion) pharmacokinetic profile, toxicity potential, and molecular docking interaction. Phytochemical screening revealed the presence of alkaloids, flavonoids, terpenoids, and tannins. GC-MS analysis identified stigmast-4-en-3-one (32.76%) and 4',6'-dimethoxy-2'-hydroxy-3-nitrochalcone (14.82%) as the major components. The extract exhibited significant antimicrobial activity against Candida albicans (18.0±0.44 mm), Escherichia coli (19.4±0.57 mm), Pseudomonas aeruginosa (23.5±1.32 mm), and Staphylococcus aureus (21.2±0.47 mm). The in vitro antidiabetic test using the ?-glucosidase enzyme showed that the n-hexane extract of M. depressa had an IC50 value of 17.561±0.471 ppm. ADMET analysis indicated that the major components followed Lipinski’s rule, exhibited drug-like properties, and were non-mutagenic. Molecular docking results showed strong interactions between the major compounds and maltase-glucoamylase (2QMJ) and PPAR-? (2Q5S). These findings suggest that the n-hexane extract of M. depressa leaves has promising antimicrobial and antidiabetic potential.